Isolasi Khamir Fermentatif dari Batang Tanaman Tebu (Saccharum officinarum. L) dan Hasil Identifikasinya Berdasarkan Sekuens Internal Transcribed Spacer - Anggraini, Ika Anggraini; Ferniah, Rejeki Siti; Kusdiyantini, Endang (Berkala Bioteknologi, 2019)
Yeast is a single-celled fungus that acts as epiphytes, endophytes or parasites. Yeast is divided into fermentative yeast and oxidative yeast. Fermentative yeast can produce primary and secondary metabolites. The role of fermentative yeast is widely used in the food industry, health and energy, so necessary to be explore fermentative yeast from sugarcane stems. The purpose of this study was to isolate fermentative yeast from sugarcane stems and identify molecular yeast based on the Internal Transcribed Spacer sequences (ITS). Isolation of epiphytic and endophytic yeast was carried out by spread plate of water soak sugarcane and sugar cane juice. Yeast isolation using 2 media, PDA and YGP with chloramphenicol. Morphological characterization was carried out by observing macroscopic and microscopic characteristics. Biochemical characterization was carried out by carbohydrate fermentation test and 50% glucose media growth test. Selected isolates were molecularly identified using Internal Transcribed Spacer (ITS) sequences. Primers used are ITS 1 and ITS 4. Phylogenetic analysis using Neighbor Joining from MEGA-6 program. The results of isolation obtained 7 yeast isolates characterized morphologically and biochemically. The based result of morphology and biochemical characterization were found 1 selected isolate with name Ed 1B. Selected yeast isolate have characteristics are round colonies, creamy white, shiny surface, raised elevation, wavy edges, ovoid cell shape, cell diameter 4,74µm, budding, glucose fermentation and sucrose fermentation, but not for lactose and grow well of 50% glucose media. The results of the Basic Alignment Search Tools (BLAST) are Ed 1B isolates had 99% homology with Kodamaea ohmeri species. Key Words : Sugarcane (Saccharum officinarum. L.), Yeast, Molecular Identification